(untitled) (Bangladesh Veterinarian, 2010)
Three different concentrations of clove oil were applied to two different size groups of singhi (Heteropneustes fossilis) and lata (Channa punctatus) fish to observe the anaesthetic effect and to find an optimum dose. Two groups each consisting of 10 fish was exposed to 0.01, 0.02 and 0.03% clove oil. All fish of either size anaesthetized with 0.01% clove oil exhibited longer induction and shorter recovery period. Exposure to 0.03% concentration of clove oil produced shorter induction and longer recovery period. The smoothness of induction of anaesthesia and recovery was the best in all groups with 0.02% clove oil. There was no mortality encountered with 0.01% and 0.02% concentration. Exposure to 0.03% of clove oil produced 20% mortality in larger singhi. In smaller and larger lata, the mortality rate was 60 and 50%, respectively. Clove oil (0.02%) appeared to be a suitable agent for anaesthesia in these two species of fish. DOI: 10.3329/bvet.v26i2.4953 Bangl. vet. 2009. Vol. 26, No. 2, 68-73